Guaranteeing Safety Despite Physical Errors in Cyber-Physical Systems - Han, Jongwoo; Park, Seonghyeon; Jeon, Haejoo; Lee, Chang-Gun (Proceedings / IEEE Real-Time and Embedded Technology and Applications Symposium, 2022)
This paper considers a cyber-physical system with a so-called "self-looping" node that repeats the inner-loop for physical situation awareness, i.e., more loops for more harsh physical situations. Regarding such a self-looping node, we observe the existence of physical errors that make the looping useless and eventually cause a critical failure. To prevent such a critical failure despite a physical error, this paper proposes a novel mechanism by introducing "time wall" and "safety backup". The time wall limits the time budget for the self-looping node so as to switch to the safety backup while still meeting the deadline to prevent critical failure despite physical errors. Our experiments through both simulation and actual implementation show that the proposed mechanism gives a comparable accuracy with the existing methods in normal cases while completely preventing the critical failure in physical error cases.